Effect of grazing hour on growth performance of crossbred sheep from southwest coastal region of Bangladesh - Sun, Minhazul Abedin; Rahman, Seam; Islam, Sarder Safiqul; Islam, Md Shafiqul; Mondol, Dhiman; Rahman, Md Mustajabur (International Journal of Agricultural Research, Innovation and Technology, 2024)
Sheep are small ruminants that require small amounts of feed and can graze on poor-quality pastures, including fallow lands, roadsides, dikes and playgrounds. Therefore, the experiment was conducted to evaluate the effect of the grazing length on growth performance of crossbred sheep in the southwestern region of Bangladesh. Sixteen crossbred female sheep were divided into four treatment groups and randomly allowed four different grazing periods. The experimental design was based on a randomized complete block design (RCBD). Lambs were initially weighed and grouped by keeping the average weight of the four treatment groups approximately the same. The grazing hours allocated to the four treatment groups were 6, 8, 10 and 12 hours, respectively. During this period, the sheep of particular treatment groups were housed when their allocated grazing period was completed. Empty body weight data were taken fortnightly in the morning before they were allowed to graze. The results revealed that body weight increased with increasing grazing length but the mean difference did not differ significantly (p>0.05). In most cases, the highest body weight was observed in sheep grazing for 12 hours per day. Average growth rates of grazing sheep varied significantly between the 6 to 8 hour and 10 to 12 hour grazing groups. But between the 6 to 8 hour grazing group and the 10 and 12 hour grazing group, the growth rate of crossbred sheep did not vary significantly (p>0.05). The growth rate (g day-1) of crossbred sheep ranged from 22.44±4.75 to 92.00±11.95, highest in 12 hour grazing group and lowest in 6 hour group. It can be concluded that the body weight and growth rate of crossbred sheep increased with an increase in grazing length. However, 10 hours of grazing meets the requirements for their maintenance and growth due to good pasture quality. Int. J. Agril. Res. Innov. Tech. 14(1): 104-107, June 2024